Capital Reserve Strategies for Residential Construction Projects through Gold-Based Fund Allocation: (Case Study of Housing Project in Pekanbaru City) - Muhammad Rilly Aka Yogi; Rian Trikomara Irana (Yayasan Inovasi Kemajuan Intelektual, 2026)
Housing development project financing generally still relies on interest-based banking mechanisms, which consequently increase the burden of capital costs. On the other hand, construction business actors are required to manage their reserve funds independently to prevent the erosion of fund value due to inflation and rising construction costs. This study aims to analyze the effectiveness of a capital reserve strategy through allocating funds into gold as a value preservation instrument in residential housing development. The research employs a quantitative descriptive approach and comparative analysis using secondary data, including the 2016 Unit Price Analysis (AHSP) and the latest 2024 AHSP, as well as historical gold price data for the period 2016–2024. The case study focuses on the construction of type 36, 45, 56, and 70 houses in Pekanbaru City. The results indicate that the increase in construction costs based on the updated AHSP is relatively conservative and does not impose excessive capital burdens. Furthermore, converting construction costs into gold-equivalent units reveals a potential surplus of up to 55.96%. These findings suggest that allocating funds to gold can serve as an effective long-term financing strategy for contractors and investors in the housing sector, particularly in preserving fund value and improving project financing efficiency.